Age- and Sex-Differences in Cardiac Characteristics Determined by Echocardiography in Masters Athletes - Wooten, Savannah V.; Moestl, Stefan; Chilibeck, Phil; Alvero Cruz, José Ramón; Mittag, Uwe; Tank, Jens; Tanaka, Hirofumi; Rittweger, Jörn; Hoffmann, Fabian (Frontiers in Physiology, 2021)
Background Cardiac function and morphology are known to differ between men and women. Sex differences seen with echocardiography have not been studied systematically in masters athletes. Purpose To evaluate sex differences in cardiac structure, function and left ventricular (LV) systolic global longitudinal strain among masters athletes. Methods This cross-sectional study comprises of 163 masters athletes (M = 109, 60 ± 12 years; F = 55, 57 ± 12 years, range 36–91 years) who participated at the 23rd World Masters Athletics Championship held in Málaga, Spain. All athletes underwent state-of-the-art echocardiography including cardiac function, morphology, strain and hemodynamic assessment. Results Left ventricular mass was higher in male than in female athletes (174 ± 44 vs. 141 ± 36 g, p < 0.01) due to greater end-diastolic intraventricular septal, LV posterior wall and LV basal diameter. However, LV mass index did not differ between the groups. End-diastolic LV volume and right ventricular area, both indexed to body-surface-area, were greater in men than in women (52.8 ± 11.0 vs. 46.1 ± 8.5 ml/m2, p < 0.01, 9.5 ± 2.4 vs. 8.1 ± 1.7 cm2/m2, p < 0.01). In contrast, women had higher LV systolic global longitudinal strain (-20.2 ± 2.6 vs. -18.8 ± 2.6%, p < 0.01) and LV outflow tract flow velocity (75.1 ± 11.1 vs. 71.2 ± 11.1 cm/s, p = 0.04). Systolic and diastolic blood pressure, LV ejection fraction, and stroke volume index were not different between sexes. Conclusion Cardiac sex differences are present even among masters athletes. Lifelong exercise training does not appear to exasperate morphological difference to a point of cardiac risk or dysfunction in both male and female athletes.